High pressure as a novel tool for the cationic ROP of γ-butyrolactone. Issue 55 (28th October 2021) - Bernat, Roksana; Maksym, Paulina; Tarnacka, Magdalena; Malarz, Katarzyna; Mrozek-Wilczkiewicz, Anna; Biela, Tadeusz; Golba, Sylwia; Kamińska, Ewa; Paluch, Marian; Kamiński, Kamil
Abstract : Well-defined poly(γ-butyrolactone) was synthesized with great efficiency via high pressure assisted cationic ROP of hardly polimerizable γ-butyrolactone. Abstract : In this study, we report the acid-catalyzed and high pressure assisted ring-opening polymerization (ROP) of γ-butyrolactone (GBL). The use of a dually-catalyzed approach combining an external physical factor and internal catalyst (trifluoromethanesulfonic acid (TfOH) or p -toluenesulfonic acid (PTSA)) enforced ROP of GBL, which is considered as hardly polymerizable monomer still remaining a challenge for the modern polymer chemistry. The experiments performed at various thermodynamic conditions ( T = 278–323 K and p = 700–1500 MPa) clearly showed that the high pressure supported polymerization process led to obtaining well-defined macromolecules of better parameters ( M n = 2200–9700 g mol −1 ; Đ = 1.05–1.46) than those previously reported. Furthermore, the parabolic-like dependence of both the molecular weight ( M W ) and the yield of obtained polymers on variation in temperature and pressure at either isobaric or isothermal conditions was also noticed, allowing the determination of optimal conditions for the polymerization process. However, most importantly, this strategy allowed to significantly reduce the reaction time (just 3 h at room temperature) and increase the yield of obtained polymers (up to 0.62 gPGBL /gGBL ). Moreover, despite using a strongly acidic catalyst, synthesized polymers remained non-toxic and biocompatible, as proven by the cytotoxicity test we performed in further analysis. Additional investigation (including MALDI-TOF measurements) showed that the catalyst selection affected not only M W and yield but also the linear/cyclic form content in obtained macromolecules. These findings show the way to tune the properties of PGBL and obtain polymer suitable for application in the biomedical industry.